PENGARUH MOTIVASI KUALITAS, MOTIVASI KARIR, MOTIVASI EKONOMI DAN MOTIVASI SOSIAL TERHADAP MINAT MAHASISWA AKUNTANSI UNTUK MENGIKUTI PENDIDIKAN PROFESI AKUNTANSI (PPAK) (STUDI KASUS PADA MAHASISWA AKUNTANSI DI STIE PELITA NUSANTARA SEMARANG) - HUDA, MUHAMMAD MIFTAHUL (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2023)
This research aims to test and analyze influence of quality motivation, career motivation, economic motivation and social motivation on accounting students interest in taking professional accounting education (PPAk). The dependent variable in this research is Accounting Students Interest in Pursuing Professional Accounting Education. The research uses primary data origionating from distributing questionnaires. The population in this study were accounting students at STIE Pelita Nusantara Semarang. The sampling technique used was census and the sample size was 68 students. The data analysis method uses the SPSS 26 program. The results of this study indicate that social motivation has a positive and significant effect on accounting students' interest in pursuing professional accounting education with a significance level of (0.002), while quality motivation, career motivation, economic motivation do not have a positive and significant effect on accounting students' interest in pursuing education. Accounting profession with a significance level of quality motivation of (0.349), career motivation of (0.466) and economic motivation of (0.105). The results of quqlity motivation, career motivation, economic motivation and social motivation simultaneously have a positive and significant effect on accounting students interst in pursuing professional accounting education with a significant level of (0,000). Keywords: quality motivation, career motivation, economic motivation, social motivation and accounting students interest in taking accounting professional education